2011
DOI: 10.1029/2010jd015525
|View full text |Cite
|
Sign up to set email alerts
|

Impact of global dimming and brightening on reference evapotranspiration in Greece

Abstract: [1] In this study, the consistency of trends in radiation and temperature records and their implications for the hydrological cycle and especially the trends in reference evapotranspiration are examined during the period 1950-2001. The new reference evapotranspiration model for complex terrains (REMCT), with monthly time step, is used for estimating trends of reference evapotranspiration in Greece. REMCT is applied after developing a methodology for calibrating its parameter values with Penman-Monteith estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 108 publications
6
31
0
5
Order By: Relevance
“…Equally, this increase in pan evaporation is also in line with a widespread increase in potential evaporation reported over the Mediterranean since the 1980s (e.g. Matsoukas et al 2011, Papaioannou et al 2011, for review see Vicente-Serrano et al 2014b).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Equally, this increase in pan evaporation is also in line with a widespread increase in potential evaporation reported over the Mediterranean since the 1980s (e.g. Matsoukas et al 2011, Papaioannou et al 2011, for review see Vicente-Serrano et al 2014b).…”
Section: Discussionsupporting
confidence: 52%
“…The important role of surface solar radiation to drive evaporation is well known, and, consequently, a link between the dimming/brightening phenomenon (Wild 2009) and the trends in actual and potential evaporation has been shown in previous studies (Roderick & Farquhar 2002, Wild et al 2008, Teuling et al 2009, Fu et al 2009, Papaioannou et al 2011. In fact, both solar radiation (Sanchez-Lorenzo et al 2013) and PichĂ© and pan trends in Spain since the mid-1980s seem to agree, not only qualitatively, but also quantitatively.…”
Section: Discussionsupporting
confidence: 49%
“…In Greece, non-significant increases in E pan over 1983-1999 were observed for a pooled series from 14 stations (Papaioannou et al, 2011). Three out of eight sites in Ireland showed a significant increase in E pan over 1963-2005, and one site showed a significant decrease (Stanhill and Möller, 2008).…”
Section: Drivers Of the Observed Changes In Catchment Evapotranspirationmentioning
confidence: 94%
“…In Europe, most studies found increasing trends of E pan (e.g. Ireland (1963Ireland ( -2005 (Stanhill and Möller, 2008), England (1957-2004 and 1986 (Stanhill and Möller, 2008;Clark, 2013), Greece (1983Greece ( -1999 (Papaioannou et al, 2011), and the Czech Republic (Trnka et al, 2015)). In this paper, we use the term atmospheric conditions to summarize the drivers available energy and atmospheric demand.…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil hĂĄ poucos trabalhos sobre tendĂȘncia na velocidade do vento (Alencar et al, 2011;. McVicar et al (2012) relatam que em vĂĄrios estudos tem-se procurado entender as causas da dinĂąmica de evapotranspiração sem considerar as tendĂȘncias da velocidade do vento (Golubev et al, 2001;Silva, 2004;Papaioannou et al, 2011). Isto Ă©, implicitamente, os autores consideram que a velocidade do vento nĂŁo apresenta tendĂȘncia.…”
Section: Resultsunclassified